A novel ultra-high-temperature oxidation protective MoSi2-TaSi2 ceramic coating for tantalum substrate. Issue 7 (July 2019) - Cai, Zhenyang; Zhang, Daxu; Chen, Xinxiang; Huang, Yuntong; Peng, Yuqing; Xu, Canhui; Huang, Siyu; Pu, Rong; Liu, Sainan; Zhao, Xiaojun; Xiao, Lairong
Abstract: To protect refractory metal against oxidation at ultra-high temperatures, a MoSi2 -TaSi2 ceramic coating was prepared on a pure tantalum (Ta) substrate using a novel three-step process, which included dip-coating with a molybdenum slurry, vacuum sintering, and halide-activated pack cementation (HAPC). The original coating had a MoSi2 -TaSi2 double-layer structure from the surface to the substrate. After oxidation at 1700°C for 8 h in air, the coating exhibited a complex multi-layer structure composed of SiO2 -Mo5 Si3 -MoSi2 -(Mo, Ta)5 Si3 -TaSi2 -Ta5 Si3 from the outer layer to the inner layer, due to the high-temperature phase transition and diffusion of Si and O. The coating effectively protected the Ta substrate at 1700°C for 12 h without failure, thereby demonstrating great improvement to its service life in an ultra-high-temperature aerobic environment. The protective effect was attributed to the integrity of the ceramic coating and the formation of a dense, uniform SiO2 film that effectively lowered the inward oxygen diffusion rate.